Leadership position as a predictor of professional success of a future teacher of higher education - Kostyria, Iryna (My University, 2020)
The aim of the publication is to present the results of a study of the correlation between leadership position indicators of future teachers of higher education and their potential professional success, which was assessed using the expert assessment method. It is specified that the leadership position of a future higher education lecturers is a personal formation, which includes a future professional's awareness of the readiness to fulfill the role of a leader and the ability to organizational impact on the teaching staff. The empirical study (n = 58) revealed statistically significant correlations between all the research constructs, which confirmed the need to develop a focused program to form a leadership position for future higher education lecturers.

Презентация результатов исследования взаимосвязи между показателями лидерской позиции будущих педагогов высшей школы и их потенциальной профессиональной успешности, которая оценивалась с помощью метода экспертной оценки. Конкретизировано, что лидерская позиция будущего педагога высшей школы представляет собой личностное образование, включающее в себя осознание будущим профессионалом готовности к выполнению роли лидера и способности к организационному воздействию на учебный коллектив.
Keywords: future lecturers; higher education institutions; leadership; leadership position; будущие педагоги; высшая школа; лидерство; лидерская позиция